An analysis of endodontic treatment with three nickel‐titanium rotary root canal preparation techniques - Ove A. Peters; F Barbakow; Christine I. Peters (2004)
Abstract Aim To investigate clinical results of root canal treatment performed with the aid of nickel‐titanium (NiTi) rotary instruments. Summary A total of 179 patients underwent root canal treatment with either (A) Lightspeed, or (B) ProFile .04 or (C) ProFile .04 and .06 or GT rotary instruments to create tapered preparations. In groups A and B, laterally condensed gutta‐percha and AH Plus were used. Canals in group C were obturated with System B, Obtura II and Roth's 801 sealer. Initial and recall radiographs were assessed using the periapical index (PAI). Outcomes were analysed using chi‐square tests, event‐time analyses and logistic regression models. Two hundred and thirty‐three teeth were radiographically assessed after a mean interval of 25.4 ± 11.8 months. Favourable outcome of treatment, defined as PAI < 3 at recall was 86.7%. Logistic regression analysis and univariate analyses indicated that teeth with preoperative PAI scores >2 and retreated teeth had a significantly lower chance of healing compared with periapically healthy teeth and primary treatments, respectively. Preparation technique, length of fill and the type of sealer did not significantly affect healing rates. Key learning points • Root canal treatment with NiTi root canal instrumentation systems renders favourable outcomes in more than 86% of the cases. • Outcome is significantly affected by preoperative diagnoses but not by the specific choice of instrumentation system.